Indian Muslims’ support for Ottoman Pan-Islamism: the case of Shibli Nu’mani - Islam, Arshad (2018)
Following their violent suppression of the Indian Revolution of 1857, the British founded and consolidated their secular empire in the Indian Subcontinent, which marginalized and bypassed religion as far as possible, particularly Islam, which had been the official religion of the Mughal ancien régime. Contemporaneous Ottoman efforts to counter European imperialism led to Sultan Abdul Hamid II’s (r. 1876-1909) policy of pan-Islamism, particularly the call for Islamic unity against the Russian aggression against Turkey in 1877. It was at this critical juncture that some Indian Muslim scholars gallantly volunteered to counter this threat, and to preserve the Islamic faith and heritage worldwide, despite the severe problems faced by the Muslims in India itself. This study highlights the role of an eminent scholar in this movement, namely Allama Shibli Nu’mani (1857-1914), who in 1914 conceived the idea of founding the world-famous Islamic research institute Darul Musannefin Shibli Academy in his home town of Azamgarh, Uttar Pradesh, India. Shibli was very active and instrumental in collecting donations from the wealthy landowners (zamindars) among the Muslim elite in his hometown of Azamgarh for the Ottoman cause, raising 3,000 rupees, which was handed to Husain Hasib Afendi, the Ottoman Consul in Bombay in 1877. Furthermore, his eloquent poetry rallied Muslims across India to support the valour and heroism displayed in the jihad by Ghazi Usman Pasha against the Russians. Shibli travelled to Istanbul in 1892 and met with the Pasha, on whose efforts Tamgha-i Majidi (gold medal) was granted to Shibli on 13th Muharram, 1310/7th August, 1892. This article is based on Shibli’s major works in Urdu, particularly his arousing eulogies (qasaid), Turkish archival reports, newspapers and magazines, and secondary sources in Urdu and English.